Scheduling and routing of automated guided vehicles - Qiu, Ling. (2008)
Automated Guided Vehicles (AGVs) have been applied in industry for several decades. However, scheduling and routing a great number of AGVs (e.g., in the order of hundreds) concurrently has not yet been studied intensively, and congestion and deadlocks arising from the routing process have not been resolved satisfactorily. In this thesis, we aim to study and develop effective algorithms that can schedule and route a large number of AGVs concurrently while resource conflicts can be prevented.